2014
DOI: 10.1186/1471-2458-14-461
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of self-report tools for physical activity research: the Physical Activity Questionnaire (PAQ)

Abstract: BackgroundThe utility of self-report measures of physical activity (PA) in youth can be greatly enhanced by calibrating self-report output against objectively measured PA data.This study demonstrates the potential of calibrating self-report output against objectively measured physical activity (PA) in youth by using a commonly used self-report tool called the Physical Activity Questionnaire (PAQ).MethodsA total of 148 participants (grades 4 through 12) from 9 schools (during the 2009–2010 school year) wore an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 42 publications
1
73
1
Order By: Relevance
“…An attractive option is to correct for self-report bias in a calibration procedure and use the corrected exposure values for further analyses. Calibration, or exposure modeling, is an established method for correcting self-reported information in the field of nutritional and body composition (41,42) and in occupational hygiene (43)(44)(45), and it is becoming increasingly popular in the field of physical activity (46)(47)(48)(49), even in an occupational context (50)(51)(52). The present study contributes to the development of effective models for estimating "true" sedentary time and time in MVPA by identifying a number of factors that may, in addition to the self-reported exposure in its own right, influence the extent of self-report bias, and that may, therefore, be candidates for inclusion in calibration models.…”
Section: Gupta Et Almentioning
confidence: 99%
“…An attractive option is to correct for self-report bias in a calibration procedure and use the corrected exposure values for further analyses. Calibration, or exposure modeling, is an established method for correcting self-reported information in the field of nutritional and body composition (41,42) and in occupational hygiene (43)(44)(45), and it is becoming increasingly popular in the field of physical activity (46)(47)(48)(49), even in an occupational context (50)(51)(52). The present study contributes to the development of effective models for estimating "true" sedentary time and time in MVPA by identifying a number of factors that may, in addition to the self-reported exposure in its own right, influence the extent of self-report bias, and that may, therefore, be candidates for inclusion in calibration models.…”
Section: Gupta Et Almentioning
confidence: 99%
“…Respondents are asked to recall the frequency and type of physical activity they have engaged in on each of the seven days prior to completing the questionnaire. Validation studies have found the PAQ-C to be highly reliable (Saint-Maurice, Welk, Beyler, Bartee, & Heelan, 2014).…”
Section: Physical Activity Maximal Oxygen Uptake and Screen Timementioning
confidence: 99%
“…Explicit prediction models have been proposed before to predict time spent sedentary and in physical activity (23)(24)(25), but these studies have not developed models for exposures at work, which may show associations with self-reported predictors other than leisure time exposures. A few previous studies have, indeed, developed prediction models for time spent sedentary and in physical activity specifically at work (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%